Autologous endothelialized small-caliber vascular grafts engineered from blood-derived induced pluripotent stem cells. (1st October 2019) - Generali, Melanie; Casanova, Elisa A.; Kehl, Debora; Wanner, Debora; Hoerstrup, Simon P.; Cinelli, Paolo; Weber, Benedikt
Graphical abstract: Abstract: An ideal cell source for human therapeutic and disease modeling applications should be easily accessible and possess unlimited differentiation and expansion potential. Human induced pluripotent stem cells (hiPSCs) derived from peripheral blood mononuclear cells (PBMCs) represent a promising source given their ease of harvest and their pluripotent nature. Previous studies have demonstrated the feasibility of using PBMC-derived hiPSCs for vascular tissue engineering. However, so far, no endothelialization of hiPSC-derived tissue engineered vascular grafts (TEVGs) based on fully biodegradable polymers without xenogenic matrix components has been shown. In this study, we have generated hiPSCs from PBMCs and differentiated them into αSMA- and calponin-positive smooth muscle cells (SMCs) as well as endothelial cells (ECs) positive for CD31, vWF and eNOS. Both cell types were co-seeded on PGA-P4HB starter matrices and cultured under static or dynamic conditions to induce tissue formation in vitro . The resulting small diameter vascular grafts showed abundant amounts of extracellular matrix, containing a thin luminal layer of vWF-positive cells and a subendothelial αSMA-positive layer approximating the architecture of native vessels. Our results demonstrate the successful generation of TEVGs based on SMCs and ECs differentiated from PBMC-derived hiPSC combined with a biodegradable polymer. These results pave the way for developing autologous PBMC-derived hiPSC-based vascular constructs for therapeutic applications or disease modeling. Statement of Significance: We report for the first time the possibility to employ human peripheral blood mononuclear cell (PBMC)-derived iPSCs to generate biodegradable polymer-based tissue engineered vascular grafts (TEVG), which mimic the native layered architecture of blood vessels. hiPSCs from PBMCs were differentiated into smooth muscle cells as well as endothelial cells. These cells were co-seeded on a biodegradable PGA/P4HB scaffold and cultured in a bioreactor to induce tissue formation in vitro . The resulting small diameter TEVG showed abundant amounts of extracellular matrix, containing a αSMA-positive layer in the interstitium and a thin luminal layer of vWF-positive endothelial cells approximating the architecture of native vessels. Our findings improving the generation of autologous vascular replacements using blood as an easily accessible cell source.